A graphene-mixed solid base catalyst and its preparation and application

Through the preparation method of graphene mixed solid base catalyst, the existing solid base catalyst has high thermal cost, low stability and low catalytic activity, and the efficient and low cost catalytic effect of biomass fuel synthesis is achieved.

CN119034714BActive Publication Date: 2025-04-01CHANGZHOU XINRI CATALYST CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411154343.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-08-21
Publication Date
2025-04-01
Estimated Expiration
2044-08-21

AI Technical Summary

Technical Problem

The existing solid base catalysts have high cost, low stability and low catalytic activity in the thermal preparation process, making it difficult to meet the needs of green chemistry and sustainable development.

Method used

Using a solid base catalyst mixed with graphene, the tannin acid solution was mixed with graphene oxide, ultrasonic dispersion and drying, and then reacted with CeCl3·7H2O and ZrOCl2·8H2O, and supported metal nitrates by a dual solvent impregnation method, and finally prepared under nitrogen conditions.

Benefits of technology

The prepared graphene mixed solid base catalyst has high specific surface area, thermal stability and high catalytic activity, is low in cost and can be reused, and is suitable for the catalysis of synthetic biomass fuels.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119034714B_ABST
    Figure CN119034714B_ABST
Patent Text Reader

Abstract

The invention provides a graphene-mixed solid base catalyst and its preparation and application, belonging to the field of catalytic technology. The invention disperses graphene oxide nanosheets in a tannic acid aqueous solution, and then performs ultrasound to form a uniformly dispersed graphene oxide solution, and finally obtains tannic acid-graphene oxide. Tannic acid-graphene oxide coordinated with Ce and Zr is used as a carrier, and metal nitrates are loaded by a double solvent impregnation method, and a solid base catalyst with a large number of strong basic centers is prepared by calcination. The catalyst prepared by the invention is used for catalytic synthesis of branched alkane precursors in the jet fuel range. The catalyst prepared by the invention has a high specific surface area and thermal stability; low preparation cost, high catalytic activity, and can effectively catalyze the aldol condensation reaction of low-activity substrates.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of catalytic technology, and in particular to a graphene-mixed solid base catalyst and a preparation method and application thereof. Background Art

[0002] Solid base catalysts are widely used in organic reactions such as transesterification, aldol condensation, oxidation, and reduction reactions due to their high reactivity, easy separation, and good repeatability. These reactions play a vital role in the synthesis of organic intermediates and fine chemicals. With the need for sustainable development and green chemistry in the world, solid bases provide a more economical and environmentally friendly method for synthesizing chemicals, which is highly desirable for green chemistry and sustainable development. This is a goal that is difficult to achieve with traditional production processes using liquid base catalysts, so environmentally friendly solid base catalysts have become a hot research focus.

[0003] Biomass is the only renewable organic carbon resource in nature. It is obtained directly or indirectly by absorbing carbon dioxide from the air through plant photosynthesis. It has unique advantages in the production of renewable fuels and high-value-added fine chemicals. Therefore, increasing the value of biomass platform compounds into biomass fuel precursors has very important theoretical and practical significance for the sustainable development of society.

[0004] The alkalinity of alkali metals or alkali metal oxide solid bases is generally related to the electronegativity of the metal element and the calcination temperature. The higher the calcination temperature, the stronger the alkalinity of these metal oxides. This is mainly because after the alkali metal is calcined at high temperature, the metal ions will recombine and arrange themselves, thereby producing lattice defects and increasing the electron cloud density near the lattice oxygen, thereby providing strong alkaline sites for the oxygen anions.

[0005] The solvent-free condensation of methyl isobutyl ketone (MIBK) and furfural (FA) to FMIBK is a promising method for synthesizing branched alkane precursors in the jet fuel range. However, due to the low activity of the α-H atom of methyl isobutyl ketone, this reaction can only be catalyzed by a strong solid base. The specific reaction equation is:

[0006]

[0007] Carbon material hybrid metal oxides can be prepared by calcining metal organic framework compound precursors in an inert atmosphere and at a mild temperature. The carbon and metal composites prepared from metal organic framework compounds have good electrical conductivity and corrosion resistance, forming composite materials with unique functions. This new type of carbon-based composite metal oxide can be widely used in many fields. Summary of the invention

[0008] The purpose of the present invention is to provide a graphene-mixed solid base catalyst and its preparation and application, so as to solve the technical problems of high thermal preparation cost, low stability and low catalytic activity of solid base catalyst in the prior art.

[0009] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0010] The present invention provides a method for preparing a graphene-mixed solid base catalyst, comprising the following steps:

[0011] (1) mixing a tannic acid solution with graphene oxide, and then sequentially performing ultrasonic dispersion treatment and drying treatment to obtain a solid powder;

[0012] (2) mixing the solid powder, CeCl3·7H2O and ZrOCl2·8H2O in a solvent for reaction to obtain a carrier;

[0013] (3) loading the metal nitrate onto the carrier by a double solvent impregnation method to obtain a catalyst precursor;

[0014] (4) calcining the catalyst precursor under nitrogen conditions to obtain a graphene-mixed solid base catalyst.

[0015] Furthermore, in the step (1), the mass concentration of the tannic acid solution is 1-5%, and the volume mass ratio of the tannic acid solution to graphene oxide is 140-160 mL: 0.6-1.0 g.

[0016] Furthermore, the mass volume ratio of CeCl3·7H2O to tannic acid solution is 3-7 g:140-160 mL, and the molar ratio of CeCl3·7H2O to ZrOCl2·8H2O is 1:0.5-2.

[0017] Furthermore, in step (2), the solvent is N,N-dimethylformamide, the volume mass ratio of the solvent to CeCl3·7H2O is 80-120 mL: 3-7 g, the reaction temperature is 60-100° C., and the reaction time is 10-14 h.

[0018] Furthermore, in step (3), the dual solvent impregnation method specifically includes: preheating the carrier to 130-150° C. and then immersing it in n-octane, after the carrier temperature drops to 45-55° C., adding the metal nitrate solution into the n-octane and immersing it for 10-14 hours, then evaporating the n-octane under heating conditions, and drying the obtained solid substance.

[0019] Furthermore, the heating temperature is 140-160°C, the drying temperature is 90-150°C, the drying time is 3-5h, the usage ratio of the carrier to n-octane and the metal nitrate solution is 2.5g:80-120mL:2.5mL, the metal nitrate in the metal nitrate solution is one or more of KNO3, LiNO3, NaNO3, CsNO3 and Zn(NO3)2, and the mass concentration of the metal nitrate solution is 20-40%.

[0020] Furthermore, in the step (4), the calcination temperature is 600-800° C., and the calcination time is 8-12 hours.

[0021] The invention provides a graphene-mixed solid base catalyst.

[0022] The present invention provides an application of a graphene-mixed solid base catalyst in synthesizing biomass fuel, comprising the following steps:

[0023] The branched ketones, furfural and graphene are mixed with a solid base catalyst and reacted to obtain a biomass fuel.

[0024] Furthermore, the reaction temperature is 130-150° C., and the reaction time is 5-7 hours; the amount of the solid base catalyst mixed with branched ketones, furfural and graphene is 2 mL: 0.5 mL: 0.05-0.2 g.

[0025] Beneficial effects of the present invention:

[0026] The solid base catalyst mixed with graphene calcined at 700° C. for 10 hours under nitrogen conditions has high specific surface area, thermal stability and high activity.

[0027] The graphene-mixed solid base catalyst prepared by the invention has low preparation cost, high catalytic activity, good stability and can be reused. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a scanning electron microscope image of the graphene-mixed solid base catalyst of Example 1;

[0029] Figure 2 The electron X-ray photoelectron spectrum of Zr 3d in the graphene-mixed solid base catalyst of Example 1;

[0030] Figure 3 is an electron X-ray photoelectron spectrum of Ce 3d in the graphene-mixed solid base catalyst of Example 1;

[0031] Figure 4is the electron X-ray photoelectron spectrum of C1s in the graphene-mixed solid base catalyst of Example 1;

[0032] Figure 5 is an electron X-ray photoelectron spectrum of K 2p in the graphene-mixed solid base catalyst of Example 1;

[0033] Figure 6 This is the electron X-ray photoelectron spectrum of O1s in the graphene-mixed solid base catalyst of Example 1. DETAILED DESCRIPTION

[0034] The present invention provides a method for preparing a graphene-mixed solid base catalyst, comprising the following steps:

[0035] (1) mixing a tannic acid solution with graphene oxide, and then sequentially performing ultrasonic dispersion treatment and drying treatment to obtain a solid powder;

[0036] (2) mixing the solid powder, CeCl3·7H2O and ZrOCl2·8H2O in a solvent for reaction to obtain a carrier;

[0037] (3) loading the metal nitrate onto the carrier by a double solvent impregnation method to obtain a catalyst precursor;

[0038] (4) calcining the catalyst precursor under nitrogen conditions to obtain a graphene-mixed solid base catalyst.

[0039] In the present invention, in the step (1), the mass concentration of the tannic acid solution is 1-5%, preferably 2-4%, and more preferably 2.5-3.5%; the volume mass ratio of the tannic acid solution to graphene oxide is 140-160 mL: 0.6-1.0 g, preferably 145-155 mL: 0.6-1.0 g, and more preferably 145-155 mL: 0.7-0.9 g.

[0040] In the present invention, the mass volume ratio of CeCl3·7H2O to tannic acid solution is 3-7g:140-160mL, preferably 4-6g:140-160mL, and more preferably 4-6g:145-155mL; the molar ratio of CeCl3·7H2O to ZrOCl2·8H2O is 1:0.5-2, preferably 1:0.7-1.7, and more preferably 1:0.9-1.3.

[0041] In the present invention, in the step (2), the solvent is N,N-dimethylformamide, and the volume mass ratio of the solvent to CeCl3·7H2O is 80-120 mL:3-7 g, preferably 90-110 mL:3-7 g, and more preferably 90-110 mL:4-6 g; the reaction temperature is 60-100°C, preferably 70-90°C, and more preferably 75-85°C; the reaction time is 10-14 h, preferably 11-13 h, and more preferably 11.5-12.5 h.

[0042] In the present invention, in the step (3), the dual solvent impregnation method specifically comprises: preheating the carrier to 130-150°C and then immersing it in n-octane, preferably 134-146°C, and more preferably 138-142°C; after the carrier temperature drops to 45-55°C, preferably 47-53°C, and more preferably 49-51°C; adding the metal nitrate solution to n-octane and immersing it for 10-14h, preferably 11-13h, and more preferably 11.5-12.5h; then evaporating the n-octane under heating conditions and drying the obtained solid matter.

[0043] In the present invention, the heating temperature is 140-160°C, preferably 144-156°C, and more preferably 148-152°C; the drying temperature is 90-150°C, preferably 95-145°C, and more preferably 100-140°C; the drying time is 3-5h, preferably 3.4-4.6h, and more preferably 3.8-4.2h; the amount ratio of the carrier to n-octane and the metal nitrate solution is 2.5g:80-120mL:2.5mL, preferably 2.5g:90-110mL:2.5mL, and the drying time is 3-5h, preferably 3.4-4.6h, and more preferably 3.8-4.2h. The preferred step is 2.5g:95~105mL:2.5mL; the metal nitrate in the metal nitrate solution is one or more of KNO3, LiNO3, NaNO3, CsNO3 and Zn(NO3)2, preferably one of KNO3, LiNO3, NaNO3, CsNO3 and Zn(NO3)2, and further preferably one of KNO3, LiNO3, NaNO3 and CsNO3; the mass concentration of the metal nitrate solution is 20~40%, preferably 24~36%, and further preferably 28~32%.

[0044] In the present invention, in the step (4), the calcination temperature is 600-800°C, preferably 640-760°C, and more preferably 680-720°C; the calcination time is 8-12h, preferably 9-11h, and more preferably 9.5-10.5h.

[0045] The invention provides a graphene-mixed solid base catalyst.

[0046] The present invention provides an application of a graphene-mixed solid base catalyst in synthesizing biomass fuel, comprising the following steps:

[0047] The branched ketones, furfural and graphene are mixed with a solid base catalyst and reacted to obtain a biomass fuel.

[0048] In the present invention, the reaction temperature is 130-150°C, preferably 134-146°C, and more preferably 138-142°C; the reaction time is 5-7h, preferably 5.4-6.6h, and more preferably 5.8-6.2h; the amount of the solid base catalyst mixed with branched ketones, furfural and graphene is 2mL:0.5mL:0.05-0.2g, preferably 2mL:0.5mL:0.07-0.17g, and more preferably 2mL:0.5mL:0.09-0.13g.

[0049] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0050] Example 1

[0051] (1) Tannic acid-graphene oxide loaded with 40% KNO3 basic catalyst Tan-GO-K-4:

[0052] 5 g of tannic acid was dissolved in 150 mL of water at 80° C. to form a tannic acid solution. 0.8 g of graphene oxide nanosheets were dispersed in the tannic acid solution, and then ultrasonicated to finally form a uniformly dispersed tannic acid-graphene oxide solution. The obtained solution was rotary evaporated, dried, and ground to obtain a tannic acid-graphene oxide solid powder.

[0053] The prepared tannic acid-graphene oxide solid powder, 5.25 g CeCl3·7H2O and 4.5 g ZrOCl2·8H2O were dissolved in 100 mL N,N-dimethylformamide in a molar ratio of n(Ce):n(Zr)=1:1, and reacted in an 80°C oil bath for 12 h; the prepared solid was washed and filtered, washed with water and alcohol for multiple times, and dried in an electric blast drying oven at 100°C for 4 h to obtain a carrier.

[0054] The carrier is loaded with metal nitrate by double solvent impregnation method. 2.5g of the carrier is weighed and placed in a round-bottom flask, immersed in an oil bath at 140℃ and heated for 6h. After lifting, 100mL of n-octane is immediately added to the round-bottom flask and a glass stopper is plugged in, waiting for the oil bath temperature to drop to 50℃. While waiting for the temperature to drop, 1g of KNO3 is weighed and dissolved in 2.5mL of deionized water for standby use. The round-bottom flask is re-immersed in the oil bath, and the prepared KNO3 solution is added dropwise to the n-octane, a glass stopper is plugged in, and the mixture is stirred and immersed for 12h; then the n-octane is thoroughly dried at 150℃ in the oil bath, and then dried at 120℃ in an electric blast drying oven for 4h. It is placed in an oven for drying to obtain a catalyst precursor.

[0055] The dried catalyst precursor was calcined at 700°C in a tubular furnace under nitrogen conditions for 10 h to obtain the tannic acid-graphene oxide loaded with 40% KNO3 alkaline catalyst Tan-GO-K-4.

[0056] (2) Aldol reaction of furfural and methyl isobutyl ketone

[0057] Take a 15mL reaction tube, add 0.5mL furfural, 2mL methyl isobutyl ketone and 0.1g solid base catalyst Tan-GO-K-4 into the reaction tube, mix and put into an oil bath pot at 140℃ for 6h. After 6h, take out the reactant, centrifuge at 9000rpm for 3 minutes, and analyze the conversion rate and selectivity of furfural and methyl isobutyl ketone by gas chromatography. The data processing adopts the area integration method. The yield of the target product is 94.3%.

[0058] (3) Determine the total amount of solid alkali by acid-base titration

[0059] To measure the amount of total base or soluble base, take a 15mL reaction tube, add 50mg sample and 10mL 0.1M hydrochloric acid to the reaction tube, shake the suspension at room temperature for 12h, separate the solid with a centrifuge, take 5mL of the supernatant with a pipette, add 2-3 drops of 0.5% phenolphthalein solution, and titrate the excess acid after the reaction is neutralized with 0.02M NaOH solution. The final calculation results in a base amount of 2.67mmol / g.

[0060] Example 2

[0061] The operation steps were the same as those in Example 1, except that KNO3 was replaced with LiNO3, and the other experimental conditions remained unchanged, and finally a basic catalyst Tan-GO-Li-4 with 40% LiNO3 loaded on tannic acid-graphene oxide was obtained. The yield of the final target product was 99.8%, and the amount of alkali after acid-base titration was 5.77 mmol / g.

[0062] Example 3

[0063] The operation steps were the same as those in Example 1, except that KNO3 was replaced with NaNO3, and the other experimental conditions remained unchanged, and finally a basic catalyst Tan-GO-Na-4 with 40% NaNO3 loaded on tannic acid-graphene oxide was obtained. The yield of the final target product was 99.4%, and the amount of alkali after acid-base titration was 3.92 mmol / g.

[0064] Example 4

[0065] The operation steps were the same as those in Example 1, except that KNO3 was replaced with CsNO3, and the other experimental conditions remained unchanged, and finally a basic catalyst Tan-GO-Cs-4 with 40% CsNO3 loaded on tannic acid-graphene oxide was obtained. The yield of the final target product was 90.0%, and the amount of alkali after acid-base titration was 3.25 mmol / g.

[0066] Example 5

[0067] The operation steps were the same as those in Example 1, except that KNO3 was replaced with Zn(NO3)2·6H2O, and the other experimental conditions remained unchanged, and finally a basic catalyst Tan-GO-Zn-4 with 40% Zn(NO3)2·6H2O loaded on tannic acid-graphene oxide was obtained. The yield of the final target product was 38.9%, and the amount of alkali after acid-base titration was 0.68 mmol / g.

[0068] Table 1 Operating conditions and reaction results of Examples 1 to 5

[0069] Serial number Catalyst dosage / g Reaction temperature / ℃ Target product yield / % Total alkali content / mmol / g Example 1 0.1 140 94.3 2.67 Example 2 0.1 140 99.8 5.77 Example 3 0.1 140 99.4 3.92 Example 4 0.1 140 90.0 3.25 Example 5 0.1 140 38.9 0.68

[0070] As can be seen from the above embodiments, the present invention provides a graphene-mixed solid base catalyst and its preparation and application. The present invention disperses graphene oxide nanosheets in a tannic acid aqueous solution, and then performs ultrasound to form a uniformly dispersed graphene oxide solution, and finally obtains tannic acid-graphene oxide. Tannic acid-graphene oxide coordinated with Ce and Zr is used as a carrier, and metal nitrates are loaded by a double solvent impregnation method, and calcined to prepare a solid base catalyst with a large number of strong alkaline centers. The catalyst prepared by the present invention is used for catalytic synthesis of biomass fuels. The catalyst prepared by the present invention has a high specific surface area and thermal stability; low preparation cost, high catalytic activity, and can effectively catalyze the aldol condensation reaction of low-activity substrates.

[0071] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a graphene-mixed solid base catalyst, characterized in that: The following steps are involved: (1) mixing a tannic acid solution with graphene oxide, and then sequentially performing ultrasonic dispersion treatment and drying treatment to obtain a solid powder; (2) Solid powder, CeCl3·7H2O and ZrOCl 2· 8H2O is mixed in a solvent to react and obtain a carrier; (3) loading the metal nitrate onto the carrier by a double solvent impregnation method to obtain a catalyst precursor; (4) calcining the catalyst precursor under nitrogen conditions to obtain a graphene-mixed solid base catalyst; The metal nitrate in the metal nitrate solution is one or more of KNO3, LiNO3, NaNO3 and CsNO3.

2. The preparation method according to claim 1, characterized in that: In the step (1), the mass concentration of the tannic acid solution is 1-5%, and the volume mass ratio of the tannic acid solution to graphene oxide is 140-160 mL: 0.6-1.0 g.

3. The preparation method according to claim 1 or 2, characterized in that: The mass volume ratio of CeCl3·7H2O to tannic acid solution is 3-7g:140-160mL. 2· The molar ratio of 8H2O is 1:0.5~2.

4. The preparation method according to claim 3, characterized in that: In the step (2), the solvent is N,N-dimethylformamide, the volume mass ratio of the solvent to CeCl3·7H2O is 80-120 mL: 3-7 g, the reaction temperature is 60-100° C., and the reaction time is 10-14 h.

5. The preparation method according to claim 1, characterized in that: In the step (3), the dual solvent impregnation method specifically comprises: preheating the carrier to 130-150° C. and then immersing it in n-octane; after the temperature of the carrier drops to 45-55° C., adding the metal nitrate solution into the n-octane and immersing it for 10-14 hours; then evaporating the n-octane under heating conditions, and drying the obtained solid matter.

6. The preparation method according to claim 5, characterized in that: The heating temperature is 140-160° C., the drying temperature is 90-150° C., the drying time is 3-5 hours, the usage ratio of the carrier to n-octane and the metal nitrate solution is 2.5 g: 80-120 mL: 2.5 mL, and the mass concentration of the metal nitrate solution is 20-40%.

7. The preparation method according to claim 1, 4 or 6, characterized in that: In the step (4), the calcination temperature is 600-800° C. and the calcination time is 8-12 hours.

8. Use of the graphene-mixed solid base catalyst prepared by the preparation method according to any one of claims 1 to 7 in synthesizing biomass fuels, characterized in that: The following steps are involved: Branched-chain ketones, furfural and a graphene-mixed solid base catalyst prepared by the preparation method according to any one of claims 1 to 7 are mixed and reacted to obtain a biomass fuel.

9. The use according to claim 8, characterized in that: The reaction temperature is 130-150° C., and the reaction time is 5-7 hours. The amount of the branched ketones, furfural and the graphene mixed solid base catalyst prepared by the preparation method according to any one of claims 1 to 7 is 2 mL: 0.5 mL: 0.05-0.2 g.

Citation Information

Patent Citations

  • Graphene based solid base catalyst preparation and application thereof in biodiesel production

    CN103418365A

  • Method for catalytically synthesizing biodiesel by using short nanorod-structured solid alkali

    CN107930658A